Development of Horizontal Warping Wheel Machine - Srisuk, Seranee (Recent Science and Technology, 2024)
Yarn warping preparation is called “warping”. Warping is a step in the yarn preparation process aimed at obtaining suitable yarn length and the desired number of yarn strands. Warping is both important and difficult, because the step requires labor and long periods of time in practice. This study, therefore, was aimed at solving these problems by designing a warping machine which reduces the distance that the operators need to walk during the process, rendering the warping process more convenient, less time-consuming, and less labor-intensive. This study designed a prototype of a warping machine which relied on the rotation of a horizontal, cylindrical warping wheel to wind the yarns. The wheel can rotate in both clockwise and counterclockwise directions. The warping wheel contained two main moving parts, namely, the movement of the wheel (rotating) and the movement of the ball screw with the linear guide (moving along the wheel). The utilization of the horizontal warping wheel machine demonstrated a 56.45% decrease in the time required for warp preparation, a reduction of 66.66% in the number of wheel operators, and a complete elimination of the distance operators had to walk during yarn warping, as compared to the traditional warp preparation method.